(untitled) (Research, Society and Development, 2021)
Traumatic bone cyst (TOC) is a non-neoplastic lesion delimited by a thin layer of loose connective tissue, without an epithelial lining. Its etiology and pathogenesis are uncertain, and trauma is one of the possible factors in the emergence of this intraosseous cyst. The most affected sites are long and gnathic bones. In the gnathic bones, they appear more frequently in the posterior and anterior region of the mandible, they are generally asymptomatic and discovered in routine radiographic exams. The definitive diagnosis of traumatic bone cyst is obtained by analyzing the clinical and radiographic characteristics of the lesion, as well as during the biopsy procedure and histopathological analysis. The objective of this work is to report a clinical case of traumatic bone cyst with post-surgical follow-up.